Critical Management of Recurrent Seizure at 16-year-old Primigravida with Atypical Eclampsia - HS, Putu Ari Kamanjaya; Gunawan, Febri Jaya (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2025)
Background: Atypical eclampsia can complicate the management and pose significant risks to both the mother and fetus. This case report emphasizes the critical management approach for recurrent seizures in a young primigravida. Case: A 16-year-old primigravida presented with sudden onset seizures during her third trimester of pregnancy. Initial assessments showed only a slight elevation of blood pressure and proteinuria, suggesting the presence of atypical eclampsia. Despite initially administering MgSO4, the patient still experienced a postpartum seizure. She was closely monitored and given a maintenance dose of midazolam and dexmedetomidine. After five days of treatment, the patient did not have any further convulsions and remained stable. Discussion: Teenage pregnancies increase the risk of maternal fatalities due to eclampsia. Atypical eclampsia is rare but can occur and requires a specific treatment approach. When therapy with magnesium sulfate is ineffective, midazolam and dexmedetomidine are used as alternative anti-epileptic drugs. Dexmedetomidine has a neuroprotective effect, preventing cerebral ischemia, and is effective in reducing the need for antihypertensive medication and hospitalization. Conclusion: The successful utilization of a combination of midazolam and dexmedetomidine highlights their potential as an effective therapeutic option for refractory seizures and adds to the existing treatment armamentarium for eclampsia.